Implementasi Program Gerakan Indonesia Sadar Administrasi dalam Percepatan Kepemilikan Akta Kelahiran Usia 0-18 Tahun - Listiyono Listiyono; Humaizi Humaizi; Heri Kusmanto (PERSPEKTIF, 2021)
In terms of fulfilling the rights and obligations of the residents of Langkat Regency in the field of civil registration of birth certificates, a comprehensive arrangement is needed to serve as guidelines and guidelines for all government officials in Langkat Regency. As the Minister of Home Affairs Instruction Number 470/837 / SJ 07 concerning the Administration of a Conscious Indonesia Movement (GISA) which aims to increase public awareness in the field of population administration, effective and efficient government and a competitive state. The local government is expected to fully support the program by creating an ideal ecosystem. This study aims to see the implementation of the Administrative Awareness Movement program in accelerating ownership of birth certificates aged 0-18 years in Langkat Regency. In this study, the research methodology used by the writers was a descriptive research method with a qualitative approach with the intention of focusing on the problems or phenomena that existed at the time the research was carried out. Key research informants were the Head of the Population and Civil Registry Office and the Head of the Civil Registration Division. Based on the results of the presentation and analysis of the data, it can be concluded that the implementation of the Administration Awareness Indonesia Movement program in accelerating the ownership of birth certificates aged 0-18 years in Langkat Regency is still not optimal, such as the communication process has not been maximal, limited resources, no budget for the program and there is a transition of structural officials.